2019
DOI: 10.1038/s41375-019-0464-2
|View full text |Cite
|
Sign up to set email alerts
|

CXCR5+CD8+ T cells are a distinct functional subset with an antitumor activity

Abstract: CXCR5 mediates homing of both B and follicular helper T (TFH) cells into follicles of secondary lymphoid organs. We found that CXCR5+CD8+ T cells are present in human tonsils and follicular lymphoma, inhibit TFH-mediated B-cell differentiation, and exhibit strong cytotoxic activity. Consistent with these findings, adoptive transfer of CXCR5+CD8+ T cells into an animal model of lymphoma resulted in significantly greater antitumor activity than CXCR5−CD8+ T cells. Furthermore, RNA-Seq-based transcriptional profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 62 publications
3
58
0
Order By: Relevance
“…Interestingly, recent studies have better characterized a subset of CD8 + /CXCR5 + T cells with proliferative capacity and able to infiltrate B cell follicles and inflamed tissues in the presence of chronic antigen exposure and inflammation ( 129 , 131 , 136 143 ). This subset shows heterogeneous phenotype and gene expression profile depending on the pathogenic context, still it is distinct from the CXCR5 − counterpart pool and maintain cytotoxic properties ( 144 ). In addition of being part of the TCF-1 + /PD-1 int progenitor pool ( 129 , 145 ), these cells have been described as having variable levels of exhaustion and being similar to Tfh cells ( 20 , 108 , 129 , 131 , 141 , 146 149 ).…”
Section: Emergence Of T Cell Exhaustionmentioning
confidence: 99%
“…Interestingly, recent studies have better characterized a subset of CD8 + /CXCR5 + T cells with proliferative capacity and able to infiltrate B cell follicles and inflamed tissues in the presence of chronic antigen exposure and inflammation ( 129 , 131 , 136 143 ). This subset shows heterogeneous phenotype and gene expression profile depending on the pathogenic context, still it is distinct from the CXCR5 − counterpart pool and maintain cytotoxic properties ( 144 ). In addition of being part of the TCF-1 + /PD-1 int progenitor pool ( 129 , 145 ), these cells have been described as having variable levels of exhaustion and being similar to Tfh cells ( 20 , 108 , 129 , 131 , 141 , 146 149 ).…”
Section: Emergence Of T Cell Exhaustionmentioning
confidence: 99%
“…fCD8s are associated with HIV and tumour control (16,18), but their differentiation conditions in humans are not known. Recent animal studies have defined the regulatory networks that govern the expression of CXCR5 in CD8 + T cells (16,17,22,23).…”
Section: Transcriptional and Epigenetic Factors Are Differentially Exmentioning
confidence: 99%
“…A small subset CXCR5 expressing CD8 + T cells called follicular CD8 + T cells (fCD8) has recently been described, to have the capacity to infiltrate B cell follicles and eliminate HIV infected cells or tumour cells (16)(17)(18). Human and animal studies have shown that the frequency of fCD8s inversely correlates with HIV or simian immunodeficiency virus (SIV) viral load (16,19,20), suggesting that increased infiltration of fCD8s in B cell follicles can result in enhanced immune control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In cases of B cell lymphoma, a trend of CXCR5 + CD8 + T cells directly targeting tumor cells was observed. 18 In HBV-related liver cancer, CXCR5 + CD8 + T cells are likely to be initially induced by viral responses, and then act on tumor cells. 19 As it is demonstrated in previous studies, CXCR5 + CD8 + T cell frequency is positively correlated with the overall survival of patients with various malignancies, including the malignancies mentioned above along with colorectal, 20 pancreas, 21 lung 22 and thyroid 23 cancer.…”
Section: Introductionmentioning
confidence: 99%